Supplementary Factual Data An Encyclopaedia of Land Transportation Models in Jakarta Using Multimedia Technologies - Dharmayanti, Dharmayanti; Permana, Dimas Dwi (Universitas Amikom Purwokerto, 2024)
The development of multimedia technology in various learning applications shows an increasing trend. According to the source (Head of IT Division AR & Co Indonesia)